A contribution to the experimental characterization of impedance steps in microstrip. - Masand, Kamal K. (University of Ottawa (Canada), 1976)
A sudden step change in the width of a microstrip has been characterized thorugh measurement. A resonant ring method is shown to yield high quality measurements. Inductive and capacitive components of the equivalent circuit of the step discontinuity have been measured for several step ratios. The results agree well with theoretical values available in the literature.
Keywords: Engineering, Electronics and Electrical.